Is It The Journey That Matters? A Fresh Look At The Impact of World Bank Policy Lending - Moll, Peter (The World Bank, 2018)
This paper investigates the impact of World Bank development policy operations on the quality of economic policy during the period 1998-2015. A new theoretical framework distinguishes among three effects that have been conflated hitherto: (a) marginal impacts of additional policy actions within the current year; (b) length of the policy engagement with client countries, and (c) changes over time in the marginal impact of policy actions. The analysis focuses on policy actions that are particularly relevant for the quality of economic management. Consistent with past research, robust panel estimations indicate that development policy financing has a positive effect on the quality of government economic policy. The econometric work suggests that the nature of the policy dialogue and quality of the engagement with government matter more than the sheer number of policy actions adopted. There is also tentative evidence that although the positive impact is sustained over time, the initial years of an engagement are the most productive for improvement in government economic policy. This may be linked to the fact that over time the reform program changes from 'first-generation' to more complex 'second-generation' policy actions